Axial contraction in etched optical fiber due to internal stress reduction - Lim, K.S.; Yang, H.Z.; Chong, W.Y.; Cheong, Y.K.; Lim, C.H.; Ali, N.M.; Ahmad, Harith (Optical Society of America, 2013)
When an optical fiber is dipped in an etching solution, the internal stress profile in the fiber varies with the fiber diameter. We observed a physical contraction as much as 0.2% in the fiber axial dimension when the fiber was reduced from its original diameter to ~6 µm through analysis using high resolution microscope images of the grating period of an etched FBG at different fiber diameters. This axial contraction is related to the varying axial stress profile in the fiber when the fiber diameter is reduced. On top of that, the refractive index of fiber core increases with reducing fiber diameter due to stress-optic effect. The calculated index increment is as much as 1.8 × 10−3 at the center of fiber core after the diameter is reduced down to ~6 µm. In comparison with the conventional model that assumes constant grating period and neglects the variation in stress-induced index change in fiber core, our proposed model indicates a discrepancy as much as 3nm in Bragg wavelength at a fiber diameter of ~6 µm.